Law Enforcement Through Social Media Pressure - Abdul Azis (Law and Justice, 2022)
Problems related to efforts to apply the law from the past have seized the attention of the Indonesian people because they are considered a very important phenomenon because it has the potential to have significant implications for Indonesian law which is basically still widely misused by legal practitioners. If viewed from the perspective of legal policy formulation that is correlated with various legal institutions at various levels, the performance of the work shown is categorized as not yet ideal and has not been able to realize the actual target of implementing the law. This encourages people to often express their disappointment through social media. From information and dissemination of social media news, it often develops into public opinion which in the language of social media communication is often called “viral news” which sometimes leads to the encouragement of law enforcement to act no longer because of law enforcement efforts but has become the fulfillment of public satisfaction and tends to ignore legal norms. Social media has made people sometimes change their image in the hope of getting sympathy and favorable public opinion for them so that it often becomes hyperreality, not reality anymore. Hyperreality is a form and state where you cannot distinguish between reality and fantasy. Through this paper, the researcher tries to do mini research through the socio-legal method where through this method the author seeks to explore further and at the same time explore law enforcement by not only based on the study of legal norms or doctrines, but also trying to see the full context of norms and their application. This study is solely aimed at providing an overview to the justice-seeking community that in the midst of uncertainty and rampant politicization of law enforcement, social media can be used as a force of coercion (pressure) as a means of law enforcement with justice.